KEGIATAN ZIARAH MAKAM GUS DUR DAN PENGARUHNYA TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT - Syai’in, - - (Irtifaq, 2014)
Since the death of Gus Dur and was buried in the family graveyard of Pesantren Tebuireng the many pilgrims who come to Tebuireng. It is quite an impact on the community and surrounding Tebuireng. Many traders and various efforts popping up to fulfill the needs and facilities of the pilgrims. In the future, the government plans to conjure tomb Wahid became "religious tourism park". Therefore, as a means of supporting the terminal will be built and stand for traders. The number of pilgrims who come to have an influence on economic empowerment Tebuireng and surrounding communities. Until now a pilgrimage to the tomb of activities Wahid no reflux, thus stretching the local economy and surrounding Tebuireng increasingly able to enjoy the benefits. So inevitably, a list of the names of the traders every day growing acreage alley meet Gus Dur.